Finnish pupils’ perceptions of health education as a school subject - Aira, Tuula; Välimaa, Raili; Paakkari, Leena; Villberg, Jari; Kannas, Lasse (Global health promotion, 2014)
Only a few countries have introduced health education (HE) as a stand-alone school subject. In Finland every pupil in basic education grades 7–9 takes three obligatory courses in HE. This study investigated Finnish pupils’ perceptions of the teaching and learning of HE. It also explored how school- and family-related background variables are associated with these perceptions. Nationally representative data were obtained from a 2010 school-based study on Health Behaviour in School-aged Children (HBSC). A total of 4262 pupils from 7th and 9th grades (13 and 15 years old) responded anonymously to the questionnaire. Logistic regression analysis was performed to identify the associations between perceptions of HE and school- and family-related background variables. The majority of the pupils had positive perceptions of HE. In terms of their own learning, girls’ perceptions were more positive than boys’: 86% of 13- and 15-year-old girls agreed that HE classes had taught them to think about the advantages and disadvantages of various health behaviours, whereas only 79% of boys shared this opinion. School engagement had the strongest association with perceptions of HE: the more positive the attitudes towards school, the more positive were the perceptions of HE. Older girls perceived their learning and their participation in class discussions more positively than younger ones, and older boys were more critical of the teaching than younger ones. The pupils’ educational aspirations were not associated with their perceptions of HE, and perceived family affluence was associated only with girls’ perceptions of participation in HE classes. The pupils’ feedback on HE was positive and encouraging. There is a demand for the subject in society, and HE seems to have the potential to augment young people’s positive attitudes towards health issues, and to enhance their health literacy.